PHYSICOCHEMICAL AND ORGANOLEPTIC QUALITY OF CHICKEN FRIED MEATBALLS BROILER USING FLOUR IS DIFFERENT - zulkarnain, D; Indi, A; Hafid, H; Suryaningsi, D P; Aku, A S; M, Munadi L O; Libriani, R (Universitas Tadulako, 2024)
Fried meatballs are different from meatballs in general. Usually, meatballs are served with hot sauce. However, fried meatballs with a crunchy texture can be consumed as a snack. Meatballs are generally gravy, and noodles or vegetables are added, while fried meatballs are processed through boiling and frying to extend their shelf life. The research aims to produce quality processed products by adding different flours through physicochemical and organoleptic tests that have been carried out at the Laboratory of Animal Product Processing Technology, Faculty of Animal Science, Halu Oleo University in November 2022 using a Completely Randomized Design of 5 treatments 5 repetitions by adding various types of flour with different concentrations repeated five times. The research results from adding various types of flour to fried meatballs for broiler chicken meat have a significant effect on physicochemical quality, especially pH, water holding capacity, cooking loss, and swelling capacity. In contrast, organoleptic quality significantly affects color, taste, elasticity, and general acceptance but does not significantly affect shape, texture, and aroma.